Bendamustine for the treatment of multiple myeloma in first-line and relapsed–refractory settings: a review of clinical trial data. Issue 3 (March 2015) - Palumbo, Antonio; Offidani, Massimo; Patriarca, Francesca; Petrucci, Maria Teresa; Cavo, Michele
Abstract: Multiple myeloma (MM) is a hematologic malignancy characterized by abnormal growth and/or dysregulation of plasma cells leading to the build-up of malignant plasma cells in the bone marrow and increased production of monoclonal immunoglobulins. Treatment modalities for MM include autologous stem cell transplant (ASCT), chemotherapy with conventional and immunomodulatory agents, radiation therapy and adjunct therapies. Bendamustine is a synthetic chemotherapeutic agent combining the alkylating properties of a mustard group with the activities of a benzimidazole ring, giving it a unique alkylating activity compared with other alkylating agents. Bendamustine has proven activity in both newly diagnosed and relapsed–refractory MM. Bendamustine has also demonstrated activity in MM after relapse from ASCT, and has recently been used successfully as a conditioning regimen for ASCT in combination with melphalan. Bendamustine is generally well tolerated, with the majority of adverse events being due to bone marrow suppression. Extramedullary toxicity is infrequent and usually mild.